Can Environmental Certification Conserve Forests in the Long Run? The Case of Coffee in Southwestern Ethiopia - Yuki Arai; Kitessa Hundera; Toshihide Yoshikura (Research Advances in Environment, Geography and Earth Science Vol. 7, 2024)
As the world faces serious deforestation triggered by agricultural land expansion, increasing attention is being paid to the use of certification schemes, which are designed to simultaneously promote ecologically sustainable agriculture and improve livelihood. Among such certification schemes, the Rainforest Alliance is known as one of the most widely used environmental certification programs throughout the world. Previous studies have compared the ecological impacts of certified and non-certified farmlands or evaluated the socio-economic outcomes of certification. However, few studies have assessed the long-term impacts of the certification scheme. This paper attempts to analyze the long-term outcomes of the Rainforest Alliance certification program through a case study of coffee farming practices in southwestern Ethiopia. Along with field observations and secondary data gathering, we performed in-depth qualitative interviews with key informants who were participating in the certification program. The findings showed that the Rainforest Alliance program’s conditions were not consistently followed and that some sections of the certified coffee forests had experienced deforestation or ecological degradation. The presence of members who did not take part in the certification program, government policies encouraging intensive coffee production, a lack of conservation incentives, loopholes in the auditing process, and the rapid population growth that required more land for agriculture and settlement are some of the potential causes. In order to ensure the successful use of certification programs, we recommend monitoring population growth rates and providing alternative livelihood opportunities, promoting collaboration between environmental and agricultural government authorities, conducting a more stringent on-site inspection at a landscape level, and providing more economic incentives for environmental conservation to all farmers living in or near the certified areas.